Direct torque controlled induction motor drive using modified five‐level torque controller for reduction in torque ripple. Issue 9 (1st July 2020) - Manohar, Murli; Das, Sukanta
Abstract : The work presents a modified switching strategy in a five‐level torque controller while implementing a direct torque control scheme for the induction motor (IM) drive. Apart from the presence of conventional full‐voltage vectors, the inclusion of intermediate‐ and zero‐voltage vectors brings in the modification above in a five‐level torque controller. Moreover, the estimation of flux in the scheme is done by machine current model. These adjustments result in the reduction in the torque and speed ripples; and improve the flux regulation in the low‐speed region, thereby obtaining superior low‐speed performance. The performance of the proposed scheme is exhaustively tested in MATLAB/Simulink and further by hardware experimentation with a laboratory‐type setup of 2.2 kW, two‐level voltage source inverter fed IM drive.